Investigating the role of combined acoustic-visual feedback in one-dimensional synchronous brain computer interfaces, a preliminary study - Gargiulo GD (Dove Medical Press, 2012)
Gaetano D Gargiulo,1–3 Armin Mohamed,1 Alistair L McEwan,1 Paolo Bifulco,2 Mario Cesarelli,2 Craig T Jin,1 Mariano Ruffo,2 Jonathan Tapson,3 André van Schaik31School of Electrical and Information Engineering, The University of Sydney, New South Wales, Australia; 2Dipartimento di Ingegneria Elettronica e delle Telecomunicazioni "Federico II" University of Naples, Naples, Italy; 3BENS Laboratory, MARCS Institute, The University of Western Sydney, New South Wales, AustraliaAbstract: Feedback plays an important role when learning to use a brain computer interface (BCI), particularly in the case of synchronous feedback that relies on the interaction subject. In this preliminary study, we investigate the role of combined auditory-visual feedback during synchronous µ rhythm-based BCI sessions to help the subject to remain focused on the selected imaginary task. This new combined feedback, now integrated within the general purpose BCI2000 software, has been tested on eight untrained and three trained subjects during a monodimensional left-right control task. In order to reduce the setup burden and maximize subject comfort, an electroencephalographic device suitable for dry electrodes that required no skin preparation was used. Quality and index of improvement was evaluated based on a personal self-assessment questionnaire from each subject and quantitative data based on subject performance. Results for this preliminary study show that the combined feedback was well tolerated by the subjects and improved performance in 75% of the naïve subjects compared with visual feedback alone.Keywords: brain computer interface, dry electrodes, subject feedback